Ceramic matrix composite material with negative curvature molded surface and preparation method of ceramic matrix composite material
By performing multi-stage densification of ceramic matrix composite materials with negative curvature profiles, and using technical means such as carbonization treatment and chemical vapor deposition, the problems of poor process stress and bearing capacity of ceramic matrix composite materials during densification are solved, and the high temperature strength and ablation resistance of ceramic matrix composite materials are improved.
Patent Information
- Application Number
- CN202411754272.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to effectively reduce the process stresses of ceramic matrix composite materials during densification, resulting in weak areas or cracks between layers, and poor load-bearing capacity, making it difficult to meet the needs of high temperature strength and ablation resistance.
By providing a fiber preform with a negative curvature profile, and using carbonization treatment, chemical vapor deposition method to form an interface layer, and multi-stage densification treatment method, liquid polycarbosilane and high-ceramic yield and low-viscosity ceramic precursors, the density and mechanical properties of the ceramic matrix composite material are gradually improved.
It effectively reduces process stress, avoids the emergence of weak areas and cracks between layers, improves the high-temperature strength and ablation resistance of ceramic matrix composites, and enhances its mechanical properties.
Smart Images

Figure CN119569473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials and preparation thereof, and in particular relates to a ceramic-based composite material with a negative curvature profile and a preparation method thereof. Background Art
[0002] Ceramic-based composites consist of structures such as fibers, interface layers and matrix. They have excellent mechanical strength, outstanding fracture toughness, and good high temperature resistance, oxidation resistance and ablation resistance. They are one of the main candidate materials for high-temperature structural parts of future aircraft and have broad application prospects in the aerospace field.
[0003] As the use of ceramic-based composite materials becomes wider and wider, ceramic-based composite materials with positive curvature surfaces or planes can no longer meet the requirements of certain design structures. However, compared with ceramic-based composite materials with positive curvature surfaces or planes, ceramic-based composite materials with negative curvature profiles not only have greater process stress during the densification process, resulting in interlayer weak areas or cracks in the components, but also have poor bearing capacity and are more prone to interlayer delamination and cracking when subjected to stress. Therefore, it is urgent to provide a densification process that can reduce process stress, avoid interlayer weak areas or cracks as much as possible, and improve bearing capacity to prepare ceramic-based composite materials with negative curvature profiles that have good high-temperature strength and high-temperature ablation resistance.
[0004] CN201710693281.7 discloses a method for preparing a special-shaped negative curvature composite ceramic wave-transmitting antenna cover body based on winding molding. The method is used to prepare a quartz composite ceramic antenna cover. The main problem to be solved is that wrinkles are easily generated during the weaving of the special-shaped structure in the manufacturing process of the negative curvature special-shaped structure antenna cover body product, and even the problem that negative curvature weaving cannot be performed. The method introduces a silica matrix material during the weaving process of the fiber fabric to increase the densification speed of the composite ceramic, but such a method will complicate the weaving of the fiber preform. Moreover, due to the use of silica sol, a ceramic-based composite material with ultra-high temperature resistance cannot be obtained.
[0005] CN202111271904.4 provides a negative curvature composite grid structure and a forming method thereof. The hot-melt prepreg used in the method includes an epoxy resin-based composite material system, a bismaleimide resin composite material system or a cyanate resin composite material system, and the resulting material is a resin-based composite material rather than a ceramic-based composite material.
[0006] CN202310235896.0 provides a method and device for preparing a special-shaped multi-layer three-dimensional fabric with a negative curvature profile, but this application mainly solves the problem of being unable to ensure the surface accuracy of the fabric, and does not pay attention to the densification problem of the composite material. Summary of the invention
[0007] In order to solve one or more of the above technical problems existing in the prior art, the present invention provides, in a first aspect, a method for densifying a fiber preform having a negative curvature profile, the method comprising the following steps:
[0008] (1) Providing a fiber preform having a negative curvature profile;
[0009] (2) fixing the fiber preform in a support member;
[0010] (3) performing a carbonization treatment on the fiber preform fixed in the support member to obtain a carbonized preform;
[0011] (4) forming an interface layer on the carbonized preform by chemical vapor deposition to obtain an interface layer preform;
[0012] (5) using a ceramic precursor for initial densification treatment to perform an impregnation-curing-cracking process on the interface layer preform to obtain an initial densification treatment ceramic matrix, wherein the precursor for initial densification treatment is a liquid polycarbosilane precursor;
[0013] (6) removing the support member, and then using a ceramic precursor solution for intermediate densification treatment to perform an impregnation-curing-cracking process on the initial densification treatment ceramic matrix to obtain an intermediate densification treatment ceramic matrix, wherein the ceramic precursor solution for intermediate densification treatment is a main matrix ceramic precursor solution;
[0014] (7) Performing post-densification treatment using a ceramic precursor for post-densification treatment to obtain a fiber preform and obtain a densified ceramic-based composite material having a negative curvature profile, wherein the ceramic precursor for post-densification treatment is a ceramic precursor with high ceramic yield and low viscosity.
[0015] In a second aspect, the present invention provides a ceramic matrix composite material having a negative curvature profile, wherein the ceramic matrix composite material has the following chemical formula: f / MX, where C f represents carbon fiber, M is selected from a combination of one or more of Zr, Hf and Ta; X is selected from a combination of one or more of C, N and B, and the density of the ceramic matrix composite material is 2.2 g / cm 3 Up to 3.5g / cm 3 (e.g., 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or 3.5 g / cm 3 ).
[0016] Compared with the prior art, the present invention has at least the following beneficial effects:
[0017] (1) In the initial densification stage of the ceramic-based composite material of the present invention, liquid polycarbosilane is used to prepare a ceramic matrix with good continuity, which plays a bonding role and avoids the occurrence of interlayer weak areas and cracks on the negative curvature surface during the matrix densification process.
[0018] (2) In the later densification stage of the ceramic-based composite material of the present invention, a ceramic precursor with high ceramic yield and low viscosity is used to improve the density, reduce the weak points between layers, and improve the mechanical properties of the component.
[0019] (3) The ceramic-based composite material in the present invention is fixed together with a support member such as a graphite support member during the early preparation stage, thereby not only avoiding bumps and damages during transportation, but also playing a dimensional role and significantly improving the interlayer bonding strength of the component.
[0020] (4) The process window of the method of the present invention is wide and the matrix composition can be controlled. The composite material obtained thereby has high density, high temperature resistance, antioxidant properties and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The CT image of the ceramic-based composite material prepared in Example 1 of the present application is shown.
[0022] Figure 2 The CT image of the ceramic-based composite material prepared in Comparative Example 1 of the present application is shown.
[0023] Figure 3 The CT image of the ceramic-based composite material prepared in Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0024] In order to solve one or more of the above technical problems existing in the prior art, the present invention provides, in a first aspect, a method for densifying a fiber preform having a negative curvature profile, the method comprising the following steps:
[0025] (1) Providing a fiber preform having a negative curvature profile;
[0026] (2) fixing the fiber preform in a support member;
[0027] (3) performing a carbonization treatment on the fiber preform fixed in the support member to obtain a carbonized preform;
[0028] (4) forming an interface layer on the carbonized preform by chemical vapor deposition to obtain an interface layer preform;
[0029] (5) using a ceramic precursor for initial densification treatment to perform an impregnation-curing-cracking process on the interface layer preform to obtain an initial densification treatment ceramic matrix, wherein the precursor for initial densification treatment is a liquid polycarbosilane precursor;
[0030] (6) removing the support member, and then using a ceramic precursor solution for intermediate densification treatment to perform an impregnation-curing-cracking process on the initial densification treatment ceramic matrix to obtain an intermediate densification treatment ceramic matrix, wherein the ceramic precursor solution for intermediate densification treatment is a main matrix ceramic precursor solution;
[0031] (7) Performing post-densification treatment using a ceramic precursor for post-densification treatment to obtain a fiber preform and obtain a densified ceramic-based composite material having a negative curvature profile, wherein the ceramic precursor for post-densification treatment is a ceramic precursor with high ceramic yield and low viscosity.
[0032] The following will further describe different technical solutions of the present invention in steps.
[0033] Step (1)
[0034] In step (1), the fiber preform with a negative curvature profile can be commercially available, for example, it can be customized from Nanjing Glass Fiber Research and Design Institute Co., Ltd. or Yixing Huaheng Fiber Weaving Co., Ltd. Of course, the fiber preform with a negative curvature profile can also be prepared by itself. For example, the fiber preform can be prepared on a mold, and an external load is applied to the negative curvature profile portion through the mold until the fiber preform forms the expected negative curvature profile, thereby obtaining a fiber preform with a negative curvature profile (such as an isolation segment or a liner fiber preform).
[0035] Preferably, the fiber preform is a carbon fiber preform. The fiber preform may be a needle-punched preform, a stitched preform, or a woven preform.
[0036] Step (2)
[0037] In step (2), the fiber preform is placed in a support member so as to achieve a shaping and protective effect with the help of the support member.
[0038] In some preferred embodiments, the support member may include an inner mold and an outer mold. The inner mold fits the inner profile of the fiber preform. In other words, the inner mold has an outer profile that fits the negative curvature profile of the fiber preform. In addition, the outer mold fits the outer profile of the fiber preform. In other words, the outer mold has an inner profile that fits the outer profile of the fiber preform.
[0039] Preferably, the support member is a graphite support member (i.e., a support member made of graphite material). Since the fiber preform with a negative curvature profile has a mechanical property that is more easily damaged. Therefore, in the present invention, preferably in the early stage of densification treatment (such as the initial densification treatment in the present invention), the preform with a negative curvature profile is fixed on the support frame to complete the initial densification treatment.
[0040] In the present invention, the inner mold and the outer mold of the support member can be independently composed of two parts, a left half and a right half, so as to facilitate demoulding in subsequent steps.
[0041] Preferably, the support member has a thickness of 10 mm to 30 mm, for example 10, 12, 14, 16, 18, 20, 22, 24, 26 or 30 mm.
[0042] It is further preferred that the support member is provided with gas passage holes. It is further preferred that the diameter of the gas passage holes is 4 mm to 8 mm (for example, 4, 5, 6, 7 or 8 mm), and the spacing between the holes is 25 mm to 35 mm (for example, 26, 27, 28, 29, 30, 31, 32, 33 or 34 mm). Alternatively, the spacing between the holes can be expressed as 30 (±5) × 30 (±5) mm), for example, 30 × 30, 31 × 31, 32 × 32, 33 × 33, 34 × 34 or 35 × 35 mm.
[0043] Step (3)
[0044] In step (3), the fiber preform fixed in the support member is subjected to carbonization treatment to obtain a carbonized preform. The carbonization treatment is generally carried out by high-temperature treatment to achieve the carbonization effect, so it can be called high-temperature carbonization treatment. The treatment temperature of the carbonization treatment is 1500°C to 3200°C (for example, 1500°C, 1800°C, 2100°C, 2400°C, 2700°C, 3000°C or 3200°C), and the insulation time is 2 hours to 4 hours (for example, 2, 3, or 4 hours).
[0045] In the present invention, the carbonization treatment can also remove impurities and moisture in the fiber preform.
[0046] Step (4)
[0047] In step (4), an interface layer is formed on the carbonized preform by chemical vapor deposition to obtain an interface layer preform. In some preferred embodiments, the thickness of the interface layer can be 50nm to 250nm (for example, 50, 100, 150, 200 or 250nm).
[0048] In some further preferred embodiments, the interface layer is a carbon layer or a silicon carbide layer.
[0049] The chemical vapor deposition method used in this step can be carried out in a conventional manner. For example, the chemical vapor deposition can use propane or trichloromethylsilane as a gas source, hydrogen or nitrogen as a diluent gas and a carrier gas, and deposit an interface layer (such as a carbon layer or a silicon carbide layer) at a certain temperature (such as 900° C. to 1200° C.) and pressure (such as 10 kPa to 150 kPa).
[0050] Step (5)
[0051] In step (5), the interface layer preform is subjected to an impregnation-curing-cracking process using a ceramic precursor for initial densification treatment to obtain an initial densification treatment ceramic matrix (the ceramic matrix obtained at this time is already a semi-finished product of a ceramic-based composite material), wherein the precursor for initial densification treatment is a liquid polycarbosilane precursor.
[0052] In some preferred embodiments, the viscosity of the liquid polycarbosilane is 10.0 mPa·s to 50.0 mPa·s (e.g., 10, 20, 30, 40, or 50 mPa·s). More preferably, the ceramic yield of the liquid polycarbosilane is 65.0% to 85.0% (e.g., 65%, 70%, 75%, 80%, or 85%).
[0053] The present invention has no special requirements for the impregnation and curing in this step. For example, in some embodiments, the impregnation time of the impregnation is 0.5 hours to 2.0 hours (for example, 0.5, 1.0, 1.5 or 2.0 hours), and the impregnation pressure is 1.0 MPa to 2.5 MPa (for example, 1.0, 1.5, 2.0 or 2.5 MPa). For another example, in other embodiments, the curing temperature of the curing can be 300° C. to 450° C. (for example, 300° C., 350° C., 400° C. or 450° C.), and the holding time can be 2 hours to 4 hours (for example, 2, 3 or 4 hours).
[0054] In other preferred embodiments, the pyrolysis temperature is 1000°C to 1500°C (for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C), and the insulation time is 3 hours to 5 hours (for example, 3, 4 or 5 hours).
[0055] In some other preferred embodiments, the process of impregnation-curing-cracking the liquid polycarbosilane can be repeated for 1 or 2 rounds.
[0056] The inventors have found that by using liquid polycarbosilane as a precursor for initial densification treatment, a ceramic matrix with excellent continuity can be obtained. It is speculated that this may be because the liquid polycarbosilane plays a bonding role, avoiding the occurrence of interlayer weak areas or cracks on the negative curvature surface of the fiber preform during the mid- and late-stage matrix densification process.
[0057] Step (6)
[0058] In step (6), the support member is removed, and then the initial densification treatment ceramic matrix is subjected to an impregnation-curing-cracking process using a ceramic precursor solution for intermediate densification treatment to obtain an intermediate densification treatment ceramic matrix, wherein the ceramic precursor solution for intermediate densification treatment is a main matrix ceramic precursor solution.
[0059] In other preferred embodiments, the main matrix ceramic precursor solution is selected from a main matrix ceramic precursor solution of a mixture of one or more of SiC, ZrC, HfC, TaC, ZrB2, HfB2 and TaB2.
[0060] The present invention has no special requirements for the solvent and content (or viscosity) in the main matrix ceramic precursor solution. Those skilled in the art can select it as appropriate according to the impregnation and impregnation convenience of the main matrix ceramic precursor solution and the use environment of the ceramic matrix composite material with a negative curvature profile to be prepared. Such selection is completely within the ability of those skilled in the art after reading the contents disclosed in this application.
[0061] The present invention has no special requirements for the impregnation and curing in this step. For example, in some embodiments, the impregnation time of the impregnation is 0.5 hours to 2.0 hours (for example, 0.5, 1.0, 1.5 or 2.0 hours), and the impregnation pressure is 1.0 MPa to 2.5 MPa (for example, 1.0, 1.5, 2.0 or 2.5 MPa). For another example, in other embodiments, the curing temperature of the curing can be 300° C. to 450° C. (for example, 300° C., 350° C., 400° C. or 450° C.), and the holding time can be 2 hours to 4 hours (for example, 2, 3 or 4 hours).
[0062] In other preferred embodiments, the pyrolysis temperature can be 1400°C to 1800°C (for example, 1400°C, 1500°C, 1600°C, 1700°C or 1800°C), and the insulation time can be 2 hours to 4 hours (for example, 2, 3 or 4 hours).
[0063] In other preferred embodiments, the three steps of impregnation-solidification-cracking of the ceramic precursor solution for the intermediate densification treatment can be repeated for 12 to 18 rounds (e.g., 12, 13, 14, 15, 16, 17 or 18 rounds).
[0064] Step (7)
[0065] In step (7), a post-densification treatment is carried out using a ceramic precursor for post-densification treatment to obtain a fiber preform to obtain a densified ceramic-based composite material with a negative curvature profile, wherein the ceramic precursor for post-densification treatment is a polyborosilazane precursor or a polycarbosilane precursor, etc.
[0066] In some preferred embodiments, the viscosity of the ceramic precursor for post-densification treatment is less than 50.0 mPa·s, and the ceramic yield is greater than 65.0%. Preferably, the viscosity of the ceramic precursor for post-densification treatment is 5 mPa·s to 50 mPa·s (for example, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50 mPa·s), and the ceramic yield is 65.0% to 85.0% (for example, 65%, 70%, 75%, 80% or 85%). More preferably, the ceramic precursor for post-densification treatment is a polyborosilazane precursor or a liquid polycarbosilane.
[0067] The present invention has no special requirements for the impregnation and curing in this step. For example, in some embodiments, the impregnation time of the impregnation is 0.5 hours to 2.0 hours (for example, 0.5, 1.0, 1.5 or 2.0 hours), and the impregnation pressure is 1.0 MPa to 2.5 MPa (for example, 1.0, 1.5, 2.0 or 2.5 MPa). For another example, in other embodiments, the curing temperature of the curing can be 300° C. to 450° C. (for example, 300° C., 350° C., 400° C. or 450° C.), and the holding time can be 2 hours to 4 hours (for example, 2, 3 or 4 hours).
[0068] In other preferred embodiments, the pyrolysis temperature is 1000°C to 1500°C (for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C), and the insulation time is 3 hours to 5 hours (for example, 3, 4 or 5 hours).
[0069] In other preferred embodiments, the post-densification treatment is performed using the three steps of impregnation-solidification-cracking of the ceramic precursor for one or two rounds.
[0070] In this step, the ceramic precursor for the post-densification treatment is a ceramic precursor with high ceramic yield and low viscosity for densification, which fully fills the pores and reduces the weak points, and finally obtains the ceramic-based composite material with a negative curvature profile.
[0071] It should be noted that in the present invention, there are no special requirements for the impregnation process and curing process in the "impregnation-curing-cracking" used in the initial, intermediate and late densification treatments, and the impregnation and curing processes commonly used in the art can be used. The process conditions provided in the above description of this application are for illustrative purposes only.
[0072] In a second aspect, the present invention provides a ceramic matrix composite material having a negative curvature profile, wherein the ceramic matrix composite material has the following chemical formula: f / MX, where C f represents carbon fiber, M is selected from a combination of one or more of Zr, Hf and Ta; X is selected from a combination of one or more of C, N and B, and the density of the ceramic matrix composite material is 2.2 g / cm 3 Up to 3.5g / cm 3 (e.g., 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or 3.5 g / cm 3 ).
[0073] Preferably, the composite material has one or more of the following properties: (I) the pressure bearing capacity of the inner surface is not less than 0.3 MPa (for example, 0.3, 0.5, 0.7 or 0.9 MPa); (II) the tensile strength is not less than 120 MPa (for example, 120, 140, 160, 180, 200 MPa); (III) the flexural strength is not less than 180 MPa (for example, 180, 200, 220, 240, 260 MPa).
[0074] More preferably, the composite material is obtained by the densification method described in the first aspect of the present invention.
[0075] Example
[0076] The present invention is further described below in conjunction with the examples. These examples are only used to illustrate the preferred embodiments of the present invention, and the protection scope of the present invention should not be interpreted as being limited to these examples.
[0077] Example 1
[0078] This embodiment provides a densification method for a fiber preform, thereby obtaining a ceramic-based composite material having a negative curvature profile, the densification method comprising the following steps:
[0079] (1) A fiber preform having a negative curvature profile is provided. Specifically, the fiber preform is a needle-punched carbon fiber preform customized by Nanjing Glass Fiber Research and Design Institute Co., Ltd., and the volume density of the needle-punched carbon fiber preform is 0.54 g / cm 3 .
[0080] (2) Fixing the fiber preform in a support. Specifically, the carbon fiber preform is placed in a graphite support, which includes an inner mold and an outer mold. The inner mold and the outer mold respectively fit the inner and outer surfaces of the negative curvature profile of the fiber preform to protect and maintain the shape. The graphite support has a thickness of 14 mm, and is provided with gas channel holes with a hole diameter of 6 mm and a hole spacing of 30×30 mm. The inner mold and the outer mold are composed of left and right halves.
[0081] (3) The fiber preform fixed in the support member is subjected to carbonization treatment to obtain a carbonized preform, wherein the treatment temperature of the carbonization treatment is 1800° C. and the heat preservation time is 2 hours. During the carbonization treatment, impurities and moisture in the fiber preform can be removed simultaneously.
[0082] (4) forming an interface layer on the carbonized preform by chemical vapor deposition to obtain an interface layer preform, wherein a pyrolytic carbon interface layer is deposited on the carbon fibers of the carbonized preform by chemical vapor deposition, and the thickness of the carbon interface layer is 95 nm. The specific operation of the chemical vapor deposition method is as follows: using propane as a gas source and nitrogen as a diluent gas and a carrier gas, at 1000° C. and (100 kPa), the deposition is performed for 100 hours to obtain a carbon interface layer with a thickness of 95 nm.
[0083] (5) Using a ceramic precursor for initial densification treatment, the interface layer preform is subjected to an impregnation-curing-cracking process to obtain an initial densification treatment ceramic matrix, wherein the precursor for initial densification treatment is a liquid polycarbosilane precursor: two rounds of liquid polycarbosilane impregnation-curing-cracking process are performed, the viscosity of the liquid polycarbosilane (as a precursor) is 42mPa·s, and the ceramic yield is 78%. The impregnation time is 1.0h, the impregnation pressure is 1.5MPa; the curing temperature is 350°C, the holding time is 2h; the cracking temperature is 1400°C, and the holding time is 3h.
[0084] (6) removing the support member, and then using a ceramic precursor solution for intermediate densification treatment to perform an impregnation-curing-cracking process on the initial densification treatment ceramic matrix to obtain an intermediate densification treatment ceramic matrix, wherein the ceramic precursor solution for intermediate densification treatment is a ZrC precursor solution (the solvent is xylene, and the viscosity is 95 mPa·s), and the impregnation-curing-cracking process is performed for 15 rounds, the impregnation time is 1.0 h, the impregnation pressure is 1.5 MPa, the curing temperature is 350°C, the insulation time is 2 h, the cracking temperature is 1600°C, and the insulation time is 2 h.
[0085] (7) Using a ceramic precursor for post-densification treatment to perform post-densification treatment for 2 rounds, a fiber preform is obtained to obtain a densified ceramic matrix composite material with a negative curvature profile, wherein the ceramic precursor for post-densification treatment is a polyborosilazane precursor, the viscosity of the polyborosilazane precursor is 8mPa·s, and the ceramic yield is 68.0%. The immersion time is 1.0h, the immersion pressure is 1.5MPa; the curing temperature is 350°C, the holding time is 2h; the pyrolysis temperature is 1000°C, and the holding time is 3h.
[0086] The CT image of the ceramic matrix composite material with negative curvature profile finally obtained in this embodiment is as follows: Figure 1 shown.
[0087] The performance indicators of the ceramic matrix composite material finally prepared in this embodiment are shown in Table 1.
[0088] Example 2
[0089] Example 2 is basically the same as Example 1, except that in step (6), the HfC precursor solution (solvent is n-propanol, viscosity is 103 mPa·s) is used to perform 13 rounds of impregnation-curing-cracking process on the initial densification treated ceramic substrate (semi-finished product).
[0090] The performance indicators of the ceramic matrix composite material finally prepared in this embodiment are shown in Table 1.
[0091] Example 3
[0092] Example 3 is basically the same as Example 1, except that a carbon fiber braided preform is used in step (1), and the density of the braided preform is 0.72 g / cm 3 .
[0093] The performance indicators of the material finally prepared in this embodiment are shown in Table 1.
[0094] Example 4
[0095] The process is carried out in substantially the same manner as in Example 1, except that in step (5), the viscosity of the liquid polycarbosilane is 10.0 mPa·s, and the ceramic yield is 84.0%.
[0096] Example 5
[0097] The process is carried out in a manner substantially the same as in Example 1, except that in step (7), the ceramic precursor for the post-densification treatment is a liquid polycarbosilane precursor having a viscosity of 18 mPa·s and a ceramic yield of 66.0%.
[0098] Comparative Example 1
[0099] The method is basically the same as that of Example 1, except that: in Comparative Example 1, step (2) is not included, and no graphite support is used for shaping. The CT image of the ceramic matrix composite material with a negative curvature profile finally obtained in this comparative example is as follows Figure 2 shown.
[0100] Comparative Example 2
[0101] The method is basically the same as that of Example 1, except that in this comparative example, a ZrC precursor solution (solvent is xylene, viscosity is 95 mPa·s) is used instead of the liquid polycarbosilane. The CT image of the composite material with a negative curvature profile finally obtained in this comparative example is as follows: Figure 3 shown.
[0102] Comparative Example 3
[0103] The process is carried out in substantially the same manner as in Example 1, except that step (7) is not performed.
[0104] The performance test results of the composite materials prepared in each embodiment are shown in Table 1 below.
[0105] Table 1 Performance indexes of composite materials with negative curvature profiles obtained in various embodiments
[0106]
[0107] contrast Figures 1 to 3 It can be seen that not using graphite supports for shaping and not using liquid polycarbosilane for early densification will lead to cracking of ceramic-based composite products with negative curvature surfaces.
[0108] It can be seen from the data in Table 1 that the performance indicators of the embodiments are relatively high. The inner surface pressure bearing strength of Example 3 can also meet the requirements, but is lower than that of other embodiments. It is speculated that the reason may be that the structure of this type of preform easily produces more closed pores in the composite material, resulting in an increase in the porosity of the product, which makes its pressure bearing capacity, tensile strength and bending strength not as good as those of other embodiments. In addition, the mechanical properties of Comparative Examples 1, 2 and 3, especially the inner surface pressure bearing capacity, are significantly reduced.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for densifying a fiber preform having a negative curvature profile, characterized in that: The method comprises the following steps: (1) Providing a fiber preform having a negative curvature profile; (2) fixing the fiber preform in a support member; (3) performing a carbonization treatment on the fiber preform fixed in the support member to obtain a carbonized preform; (4) forming an interface layer on the carbonized preform by chemical vapor deposition to obtain an interface layer preform; (5) using a ceramic precursor for initial densification treatment to perform an impregnation-curing-cracking process on the interface layer preform to obtain an initial densification treatment ceramic matrix, wherein the precursor for initial densification treatment is a liquid polycarbosilane precursor; (6) removing the support member, and then using a ceramic precursor solution for intermediate densification treatment to perform an impregnation-curing-cracking process on the initial densification treatment ceramic matrix to obtain an intermediate densification treatment ceramic matrix, wherein the ceramic precursor solution for intermediate densification treatment is a main matrix ceramic precursor solution; (7) Performing post-densification treatment using a ceramic precursor for post-densification treatment to obtain a fiber preform and obtain a densified ceramic-based composite material having a negative curvature profile, wherein the ceramic precursor for post-densification treatment is a ceramic precursor with high ceramic yield and low viscosity.
2. The densification method according to claim 1, characterized in that In step (1): The fiber preform is a carbon fiber preform; preferably, the fiber preform is a needle-punched preform, a stitched preform or a woven preform.
3. The densification method according to claim 1, characterized in that: In step (2): The support member comprises an inner mold and an outer mold, wherein the inner mold fits the inner surface of the fiber preform, and the outer mold fits the outer surface of the fiber preform; preferably, the support member is a graphite support member; Preferably, the inner mold and the outer mold of the support member are both composed of a left half and a right half; More preferably, the thickness of the support member is 10 mm to 30 mm; It is further preferred that the support member is provided with gas passage holes; it is further preferred that the diameter of the gas passage holes is 4 mm to 8 mm, and the spacing between the holes is 25 mm to 35 mm.
4. The densification method according to claim 1, characterized in that: In step (3): The treatment temperature of the carbonization treatment is 1500° C. to 3200° C., and the insulation time is 2 hours to 4 hours.
5. The densification method according to claim 1, characterized in that: In step (4): The thickness of the interface layer is 50nm to 250nm; Preferably, the interface layer is a carbon layer or a silicon carbide layer.
6. The densification method according to claim 1, characterized in that: In step (5): The viscosity of the liquid polycarbosilane is 10.0 mPa·s to 50.0 mPa·s, and / or the ceramic yield is 65.0% to 85.0%; The pyrolysis temperature of the pyrolysis is 1000° C. to 1500° C., and the holding time is 3 hours to 5 hours; and / or The process of impregnation-curing-cracking the liquid polycarbosilane is performed for 1 or 2 rounds.
7. The densification method according to claim 1, characterized in that: In step (6): The main matrix ceramic precursor solution is selected from a main matrix ceramic precursor solution of one or more mixed ones of SiC, ZrC, HfC, TaC, ZrB2, HfB2 and TaB2; The pyrolysis temperature of the pyrolysis is 1400°C to 1800°C, and the holding time is 2 hours to 4 hours; Preferably, the three steps of impregnation-solidification-cracking of the ceramic precursor solution for the intermediate densification treatment are repeated for 12 to 18 cycles.
8. The densification method according to claim 1, characterized in that: In step (7): The viscosity of the ceramic precursor for post-densification treatment is lower than 50.0 mPa·s, and the ceramic yield is greater than 65.0%; preferably, the viscosity of the ceramic precursor for post-densification treatment is 5 mPa·s to 50 mPa·s, and the ceramic yield is 65.0% to 85.0%; more preferably, the ceramic precursor for post-densification treatment is a polyborosilazane precursor or liquid polycarbosilane. The post-densification treatment is carried out in one or two rounds using the three steps of impregnation-solidification-cracking of the ceramic precursor.
9. A ceramic matrix composite material having a negative curvature profile, characterized in that: The ceramic matrix composite material has the following chemical formula: f / MX, where C f represents carbon fiber, M is selected from a combination of one or more of Zr, Hf and Ta; X is selected from a combination of one or more of C, N and B, and the density of the ceramic matrix composite material is 2.2 g / cm 3 Up to 3.5g / cm 3 .
10. The ceramic matrix composite material according to claim 9, characterized in that: The composite material has one or more of the following properties: (I) the pressure bearing capacity of the inner surface is not less than 0.3 MPa; (II) the tensile strength is not less than 120 MPa; (III) the bending strength is not less than 180 MPa; Preferably, the composite material is obtained by the densification method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A negative curvature composite material grid structure and forming method thereof
CN114311728B
A method and device for manufacturing a special-shaped multi-layer three-dimensional fabric with a negative curvature profile
CN116587713B
Preparation method of special-shaped negative-curvature composite ceramic wave-transparent radome body based on winding formation
CN107538599A
Special-shaped structure ceramic matrix composite radome and preparation method thereof
CN110272293A
C / SiC-HfB2 composite material and preparation method thereof
CN110627514A